Chronic Effects of Maternal Low-Protein and Low-Quality Protein Diets on Body Composition, Glucose-Homeostasis and Metabolic Factors, Followed by Reversible Changes upon Rehabilitation in Adult Rat Offspring - Pandarinath Savitikadi (MDPI AG, 2021)
Several studies suggest that the maternal protein content and source can affect the offspring’s health. However, the chronic impact of maternal quality and quantity protein restriction, and reversible changes upon rehabilitation, if any, in the offspring, remains elusive. This study examined the effects of maternal low-quality protein (LQP) and low-protein (LP) intake from preconception to post-weaning, followed by rehabilitation from weaning, on body composition, glucose-homeostasis, and metabolic factors in rat offspring. Wistar rats were exposed to normal protein (NP; 20% casein), LQP (20% wheat gluten) or LP (8% casein) isocaloric diets for 7 weeks before pregnancy until lactation. After weaning, the offspring were exposed to five diets: NP, LQP, LQPR (LQP rehabilitated with NP), LP, and LPR (LP rehabilitated with NP) for 16 weeks. Body composition, glucose-homeostasis, lipids, and plasma hormones were investigated. The LQP and LP offspring had lower bodyweight, fat and lean mass, insulin and HOMA-IR than the NP. The LQP offspring had higher cholesterol, T3 and T4, and lower triacylglycerides and glucose, while these were unaltered in LP compared to NP. The majority of the above outcomes were reversed upon rehabilitation. These results suggest that the chronic exposure of rats to maternal LQP and LP diets induced differential adverse effects by influencing body composition and metabolism, which were reversed upon rehabilitation.